2019
DOI: 10.1002/epi4.12372
|View full text |Cite
|
Sign up to set email alerts
|

The antiepileptic effect of Gastrodiae Rhizoma through modulating overexpression of mTOR and attenuating astrogliosis in pilocarpine mice model

Abstract: Objective To investigate the effect of water extract of Gastrodiae Rhizoma (GR) on the development of acquired temporal lobe epilepsy (TLE) and on regulating the expression of the mammalian target of rapamycin (mTOR) and semaphorin 3F (SEMA3F). Methods A pilocarpine‐induced status epilepticus (SE) model was adopted to precipitate injury in the limbic systems. GR and carbamazepine (CBZ) treatments were given to mice for 14 days prior to SE induction to demonstrate the antiepileptic effects and continued for 5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Herbs might have variable actions on the metabolism, absorption and transport of AEDs ( 96 ). For example, several studies have reported pharmacokinetic interactions of CBZ with different herbal medicines, such as Rhizoma Gastrodiae ( 98 , 99 ). Pharmacokinetic study in rats indicated that Rhizoma Gastrodiae could reduce the auto-induction of CBZ and increase the plasma concentration of CBZ and its metabolite, demonstrating an herb-drug interaction of Rhizoma Gastrodiae with CBZ which will provide implications for epilepsy treatment in clinic ( 98 ).…”
Section: Discussionmentioning
confidence: 99%
“…Herbs might have variable actions on the metabolism, absorption and transport of AEDs ( 96 ). For example, several studies have reported pharmacokinetic interactions of CBZ with different herbal medicines, such as Rhizoma Gastrodiae ( 98 , 99 ). Pharmacokinetic study in rats indicated that Rhizoma Gastrodiae could reduce the auto-induction of CBZ and increase the plasma concentration of CBZ and its metabolite, demonstrating an herb-drug interaction of Rhizoma Gastrodiae with CBZ which will provide implications for epilepsy treatment in clinic ( 98 ).…”
Section: Discussionmentioning
confidence: 99%
“…SE is a life-threatening emergency that is typically terminated through antiepileptic drug treatment, leading to hippocampus dysfunction typified by neurodegeneration, inflammation, and altered neurogenesis, as well as cognitive and memory deficits. An episode of extended SE is [28][29][30][31]. Neurons are abnormally excited during epileptic seizures, and neuronal excitability depends primarily on energy metabolism [16,32].…”
Section: Discussionmentioning
confidence: 99%
“…Due to these changes, a recurrent excitatory circuit formed which causes focal seizures of spontaneous recurrence and epileptic state progression. In rodent epilepsy model, semaphorins have rewiring events (Yip et al., 2020). For mossy fibers, Sema3A acts as a repellent and is delivered to entorhinal cortex neurons from the axons to the molecular layer in the outer part.…”
Section: Role Of Axon Guidance Proteins In the Animal Epilepsy Modelmentioning
confidence: 99%